Impact of spatial inhomogeneities on on-axis pulse reconstruction in femtosecond filaments. (10th April 2015) - Brée, Carsten; Kretschmar, Martin; Nagy, Tamas; Kurz, Heiko G; Morgner, Uwe; Kovačev, Milutin
Abstract: We demonstrate a strong influence of the spatial beam profile on the vacuum-propagated on-axis pulse shapes for a femtosecond filament in argon. The effects can be minimized by transmitting the filament into the far-field by a laser drilled pinhole setup. Using this method, we can monitor the pulse compression dynamics along the entire longitudinal extension of the filament, including the ionization-induced plasma channel.